Filozoficzne uwarunkowania nowoczesności w nauce - Drozdowicz, Zbigniew (Polska Akademia Nauk, 2017)
In these remarks I recall the attempts of pointing out the relations between philosophy and modernity in sciences in three distinctively differing point of view, that is the achievements of “the Enlightened Age” (in the sense of Ernst Cassirer), phenomenological philosophy (in the sense of Edmund Husserl) and the classicist conservatism (in the sense of Allan Bloom). In each of these cases an importance of those relations is being acknowledged. However it is not just differently evaluated and justified, but also the diagnoses and forecasts related to it look differently either.
Keywords: enlightenment modernity; modernity in the perspective of phenomenological philosophy; modernity from the point of view of classicist conservatism